2018
DOI: 10.1158/1541-7786.mcr-17-0662
|View full text |Cite
|
Sign up to set email alerts
|

FoxO3a Mediates the Inhibitory Effects of the Antiepileptic Drug Lamotrigine on Breast Cancer Growth

Abstract: Breast cancer is a complex and heterogeneous disease, with distinct histologic features dictating the therapy. Although the clinical outcome of breast cancer patients has been considerably improved, the occurrence of resistance to common endocrine and chemotherapy treatments remains the major cause of relapse and mortality. Thus, efforts in identifying new molecules to be employed in breast cancer therapy are needed. As a "faster" alternative to reach this aim, we evaluated whether lamotrigine, a broadly used … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…Recently published data from our laboratory suggest that a promising pharmacological candidate for such an adjuvant therapy in patients who result refractory to the antiestrogen treatment is LTG, a well-known AED that is able to increase FoxO3a levels in BCCs [28]. Thus, to evaluate if LTG, by inducing FoxO3a expression, is able to restore the sensitivity to the anti-hormonal therapy also in vivo, female nude mice bearing TamR cells-derived tumor xenografts into the intrascapular region, were treated with LTG (20 mg/kg/day) on the basis of our in vitro results [28] and on the pertinent literature [36].…”
Section: The Aed Lamotrigine Restores the Sensitivity To Tamoxifen Treatment Through Foxo3a Re-expression In Tamoxifen Resistant Xenografmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently published data from our laboratory suggest that a promising pharmacological candidate for such an adjuvant therapy in patients who result refractory to the antiestrogen treatment is LTG, a well-known AED that is able to increase FoxO3a levels in BCCs [28]. Thus, to evaluate if LTG, by inducing FoxO3a expression, is able to restore the sensitivity to the anti-hormonal therapy also in vivo, female nude mice bearing TamR cells-derived tumor xenografts into the intrascapular region, were treated with LTG (20 mg/kg/day) on the basis of our in vitro results [28] and on the pertinent literature [36].…”
Section: The Aed Lamotrigine Restores the Sensitivity To Tamoxifen Treatment Through Foxo3a Re-expression In Tamoxifen Resistant Xenografmentioning
confidence: 99%
“…In this context, here, we investigated, for the first time, the protective role of FoxO3a in the progression of ER+ BC from a sensitive to a resistant phenotype to tamoxifen treatment. Moreover, since we recently demonstrated that the antiepileptic drug (AED) lamotrigine (LTG), similarly to other AEDs [25][26][27], is able to inhibit BC growth by inducing FoxO3a expression [28], its potential use as adjuvant to tamoxifen therapy has been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Cells were plated as previously described ( Pellegrino et al, 2018 ). After 2 days, vehicle (−) or treatments (OLA at 50 and 100 μM) were added and replaced every 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…Cell lines were acquired and authenticated from Interlab Cell Line Collection (ICLC, Genova, Italy), they were tested monthly for negativity to Mycoplasma (MycoAlert, Lonza) and they were maintained as previously described (Pellegrino et al, 2018).…”
Section: Cell Culturesmentioning
confidence: 99%
“…Most anti-epileptic drugs in clinical use, including phenytoin [191][192][193], carbamazepine [194][195][196][197], lamotrigine [198], topiramate [199][200][201][202], and many others, inhibit VGSCs and show different degrees of anti-tumoral effects (for a review see Koltai [203]). From a long list of VGSC inhibitors, we have chosen topiramate because it has a quadruple action against tumors:…”
Section: Voltage Gated Sodium Channels (Vgscs) Inhibitionmentioning
confidence: 99%